1995
DOI: 10.1111/j.1528-1157.1995.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine‐GABAA Receptors in Idiopathic Generalized Epilepsy Measured with [11C]Flumazenil and Positron Emission Tomography

Abstract: The neurochemical basis of absence seizures and the mechanism of their suppression by valproate (VPA) are uncertain. We used positron emission tomography (PET) to determine whether an abnormality of [11C]flumazenil binding to benzodiazepine (BZD)-GABAA receptors exists in patients with childhood and juvenile absence epilepsy and to examine the effects of VPA on [11C]flumazenil binding. The regional cerebral volume of distribution (Vd) of [11C]flumazenil in patients not treated with VPA was not different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 43 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Reliable identification of cerebellar nuclei is not easy on 11 C-flumazenil PET images and these results have not been replicated. Prevett et al [49] found no significant difference in 11 Cflumazenil binding to cerebral cortex, thalamus or cerebellum between patients with childhood and juvenile absence epilepsy, not taking valproate, and control subjects. The volume of distribution of 11 C-flumazenil, however, was 9% less in patients receiving valproate, with a 20% reduction of receptor density, suggesting that this drug may result in a reduced number of available benzodiazepine receptors.…”
Section: Introductionmentioning
confidence: 97%
“…Reliable identification of cerebellar nuclei is not easy on 11 C-flumazenil PET images and these results have not been replicated. Prevett et al [49] found no significant difference in 11 Cflumazenil binding to cerebral cortex, thalamus or cerebellum between patients with childhood and juvenile absence epilepsy, not taking valproate, and control subjects. The volume of distribution of 11 C-flumazenil, however, was 9% less in patients receiving valproate, with a 20% reduction of receptor density, suggesting that this drug may result in a reduced number of available benzodiazepine receptors.…”
Section: Introductionmentioning
confidence: 97%
“…[276][277][278][279][280][281] The potential involvement of GABAergic transmission in the mechanisms of action of mood stabilizers and antidepressants still remains elusive, especially regarding GABA receptors. Several studies have reported that GABA A receptors are decreased after treatment with valproate, 212 antidepressants, 45,220 and even with new antipsychotics, such as olanzapine and clozapine, 267 which are also of utility in the treatment of mood disorders. As reviewed in the first section of the paper, GABA A and GABA B receptors interact with several second messengers, have different synaptical position, and elicit various neuronal effects.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…A PET study showed that valproate reduces GABA A receptor binding in young patients with absence of epilepsy compared to subjects not treated with valproate in several brain areas such as frontal cortex, temporal cortex, and basal ganglia. 212 We are not aware of any neuroimaging study that examined GABA receptors after treatment with mood stabilizers in mood disorder patients. In vivo MRS studies found an increase in human GABA levels after gabapentin, 213 topiramate, 214 and vigabatrin administration, 215 which are new anticonvulsants suggested to be effective in particular cases of mood disorders.…”
Section: Gabaergic Modulation In the Treatment Of Mood Disordersmentioning
confidence: 99%
“…Such work includes studies of seizure and epilepsy, e.g., [13][14][15][16][17][18][19][20][21][22][23][24]; stroke, e.g., [25][26][27]; hemianopia, e.g., [28]; dementia, e.g., [29][30][31][32]; depression, e.g., [33]; Parkinson's Disease, e.g., [34]; and post-traumatic stress disorder [35]. Rare diseases have also been examined, for example, the autosomal recessive disorder succinic semialdehyde dehydrogenase deficiency [36].…”
Section: Introductionmentioning
confidence: 99%